STRENGTHENING OF REINFORCED CONCRETE BEAMS USING GLASS FIBER REINFORCED POLYMER - RAMBABU, GUGULOTHU; PRUDHVIJA, PUSHADAPU; KUMAR, KUSUMA SUNDAR (IJRDO-Journal of Applied Science, 2016)
Worldwide, a great deal of research is currently being conducted concerning the use of fiberreinforced plastic wraps, laminates and sheets in the repair and strengthening of reinforced concrete membersFiber-reinforced polymer (FRP) application is a very effective way to repair and strengthen structures that havebecome structurally weak over their life span. FRP repair systems provide an economically viable alternative totraditional repair systems and materials. Experimental investigations on the flexural and shear behavior of RCbeams strengthened using continuous glass fiber reinforced polymer (GFRP) sheets are carried out. Externallyreinforced concrete beams with epoxy-bonded GFRP sheets were tested to failure using a symmetrical two pointconcentrated static loading system. Two sets of beams were casted for this experimental test program. In SET Ithree beams weak in flexure were casted, out of which one is controlled beam and other two beams werestrengthened using continuous glass fiber reinforced polymer (GFRP) sheets in flexure. In SET II three beamsweak in shear were casted, out of which one is the controlled beam and other two beams were strengthened usingcontinuous glass fiber reinforced polymer (GFRP) sheets in shear. The strengthening of the beams is done withdifferent amount and configuration of GFRP sheets. Experimental data on load, deflection and failure modes ofeach of the beams were obtained. The detail procedure and application of GFRP sheets for strengthening of RCbeams is also included. The effect of number of GFRP layers and its orientation on ultimate load carrying capacityand failure mode of the beams are investigated